Inline skating for balance and strength promotion in children during physical education - Muehlbauer, T.; Kuehnen, M.; Granacher, U. (Perceptual and Motor Skills, 2013)
Summary.—Deficiencies in balance and strength are common in children and they may lead to injuries. This study investigated the effects of inline skating exercise on balance and strength performance in healthy children. Twenty 11-12-year-old children (8 girls, 12 boys) were assigned to an intervention (n = 10) or a control (n = 10) group. Participants in the intervention group underwent a 4-week inline skating program (2 times/week, 90 min. each) integrated in their physical education lessons. Balance and strength were measured using the Star Excursion Balance test and the countermovement jump test. As compared to the control group, the intervention group significantly improved balance (17-48%, Cohen's d = 0.00-1.49) and jump height (8%, Cohen's d = 0.48). In children, inline skating is a safe, feasible (90% adherence rate), and effective program that can be integrated in physical education lessons to promote balance and strength.